Iraq Crude Oil Exports – July, August, September 2016 and Crude Oil production Rates and Gas Production Activities, Types of Oils and Asphalt - SOMO, Ministry of Oil / Oil Marketing Company (Journal of Petroleum Research and Studies, 2017)
Table 1. Iraq Crude Oil Exports – July 2016 Table 2. Iraq Crude Oil Exports – August 2016 Table 3. Iraq Crude Oil Exports – September 2016 Table 4. Crude Oil production Rates and Crude Discharge for July / 2016 Table 5. Oil Production Rates for July /2016 Table 6. Crude Oil Production Rates and Crude Discharge for August / 2016 Table 7. Oil Production Rates for August /2016 Table 8. Gas Production Activities, Types of Oils and Asphalt for July /2016 Table 9. Gas Production Activities, Types of Oils and Asphalt for August / 2016